(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
Introduction. The paper deals with the highlighting of specific features of the introduction of the model of formation of future philologists’ professional competence using Internet technologies in the educational process. For this purpose, it is necessary to solve the following tasks: 1) to perform pedagogical diagnostics of criteria and indicators of formation of future philologists’ professional competence; 2) to determine content characteristics of levels of formation of future philologists’ professional competence on the basis of the singled out criteria and indicators; 3) to implement the experimental content and methods of the additional training of students (on the basis of the author’s course "Information Technologies in the Educational Process"); 4) to diagnose levels of formation of future philologists’ professional competence by means of Internet technologies and to make a comparative analysis of the obtained results with the results of the ascertaining phase of the pedagogical experiment. Diagnostic and statistical methods of research are applied in the paper. Problem statement. Singling out the criteria and indicators of formation of future philologists’ professional competence makes it possible to diagnose the detection of the levels of this type of competence. The term "diagnosis" requires clarification of its content. It is interpreted as a recognition of a state of the certain object or system by means of quick registration of their essence parameters and their further admission to a specific diagnostic category for the prediction of their behaviour and decision-making on the expected impact on this behaviour to change it in the desired direction [5, 6]. The notion of "diagnosis" correlates with the term "diagnostic work", which, according K. Ingenkamp [4, 98], we understand the process by which the teacher, using or not using the diagnostic tools supervises students and conducts questioning, observations and works out questionnaires and reports the results to describe the behaviour, to explain their motives or to predict their behaviour in future, following the necessary scientific criteria of quality. Analysis of current researches and publications related to the problem . In our study the concept of "educational diagnosis" is actualized, which is interpreted as getting information about the state and development of the learning process, revealing conditions, advantages and disadvantages of this process, identification of ways of increasing its efficiency and improvement of vocational training in accordance to the intended purpose [8, 129]. Pedagogical diagnostics is also seen as a process, which is a part of the scientific management system, directly connected with defining knowledge and skills, development of upbringing, evaluation of the actual students’ behaviour [6, 145]. Thus, the pedagogical diagnostics is simultaneously both a special branch of pedagogical knowledge and the teacher’s specific practical activities, the task of which is to study the course and results of the pedagogical process for its improvement [2, 251]. The main aim. In this paper by pedagogical diagnostics, according to E. V. Tokar [7, 491], we mean obtaining and analysing information about the status, the development and current condition of the educational process, its results, identification of its advantages and disadvantages, factors that will influence its efficiency and performance. The purpose of pedagogical diagnostics is not only to determine the level of knowledge and skills of subjects of the educational process, but also in performing the analysis of conditions of conducting the current didactic process and their direct impact on the level of training, and in prediction of further development of the process of getting knowledge, improving future philologists’ skills, as well as management of the training process in general.